From the urban project to the participative public space project: A historical approach (2020)
This article makes a chronological tour of the main city-making models, from classic to current times, to arrive at the conclusion that citizen participation in decision-making processes on urban projects has ended up conditioning the current working models of the ter-ritory, particularly in terms of urban production. De-spite the inconsistency between what the broad body of knowledge on cities (Lexis) establishes for the develop-ment of citizenship and the often defended and cited citizen rights, and the practice (praxis) of participa-tion, we find that processes that are promoted as being inclusive and with a collective work approach end up becoming, either through omission, lack of knowledge, inexperience or despotism, models that conceal hier-archical power structures and that deny urban equity and justice in public space projects.